A Histologically Diagnosed Case with Infantile Osteopetrosis Complicated by Hypopituitarism. (20th October 2015) - Diniz, Gulden; Olukman, Ozgur; Calkavur, Sebnem; Buyukinan, Muammer; Altay, Canan
Abstract : Malignant infantile osteopetrosis is a rarely seen severe disorder which appears early in life with general sclerosis of the skeleton. It is caused by functionally defective osteoclasts which fail to resorb bone. Affected infants can exhibit a wide spectrum of clinical manifestations including impaired hematopoiesis, hepatosplenomegaly, visual impairment, and hypocalcemia. With the exception of secondary hyperparathyroidism, involvement of the endocrine system seems to be quite rare. Hypopituitarism is defined as underproduction of the growth hormone in combination with deficiencies of other pituitary hormones. Any lesion that damages hypothalamus, pituitary stalk, or anterior pituitary can cause secondary hypopituitarism. In this report, we presented a rare combination of malignant infantile osteopetrosis and secondary hypopituitarism in a newborn who presented predominantly with endocrinological symptoms. This is the first case report of malignant infantile osteopetrosis accompanied by hypopituitarism secondary to sclerosis of the sella turcica. On the other hand, this is a very interesting case which was diagnosed based on histological examination of bone marrow biopsy specimens despite lack of any clinical suspicion.